The Utilization of Vegetable Waste as Fermented Chicken Feed for Maintaining Super Native Chickens in the Young Farmer’s Group at ALC - Luh Suariani; Made Yudiastari; Yan Tonga; Ni Ketut Etty Suwitari; I Made Adi Wiratama; Agung Pamuji; I Made Deddy Dharmika (Asian Journal of Community Services, 2023)
His community service activity was carried out for the young farmer group at Agro Learning Center in Peguyangan Kangin Village, North Denpasar District, Denpasar City. This activity aims to increase the young farmers' knowledge about making fermented feed based on vegetable waste for nativee chickens. A nativee chicken is a type of local chicken widely cultivated in Indonesia. By utilizing vegetable waste which is commonly found, the breeder can produce chicken feed. Service activities are carried out by practicing making fermented feed with vegetable waste with the help of an EM4 fermenter, molasses and other feed ingredients. After fermentation, the fermented feed will be directly given to nativee chickens from the age of 3 weeks. After the post-test was carried out, it was seen that this activity could increase the training participants' knowledge about fermenting feed of vegetable waste.